The Influence of Personal Selling on Wedding Package Purchase Decisions at Six Senses Uluwatu - Aldiani, Yuke; Citrawati, Luh Putu; Kusumarini, Indah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bali has become one of the most popular wedding destinations for tourists since the end of 1999. This has caused hotels in Bali to provide wedding packages to support the needs of tourists, so there is fierce competition between hotels. To face the competition, Six Senses Uluwatu carries out various promotions including personal selling. This study aims to determine the effect of personal selling on the decision to purchase a wedding package at Six Senses Uluwatu. Research data were collected by distributing questionnaires to 56 respondents who had purchased a wedding package and held a wedding at Six Senses Uluwatu in the period 2022-2023. The data analysis techniques used were simple linear regression analysis, determination coefficient analysis (R2) and t-test assisted by the SPSS 26 program. Based on the data analysis, it is known that personal selling (X) has a positive and significant effect on the decision to purchase (Y) a wedding package at Six Senses Uluwatu. Through simple linear regression analysis, it is known that the relationship between personal selling and purchasing decisions is positive. In the t-test, the calculated t value is greater than the t-table (8.505 > 2.004), meaning that the personal selling variable has an effect on the purchasing decision variable. Based on the analysis of the determination coefficient (R2), the personal selling variable has an effect of 57.3% on purchasing decisions. While the other 42.7% is influenced by other variables not examined in this study.